Nursing in oncology ward with intertwined roles: a focused ethnography - Hadiseh Monadi Ziarat; Naima Seyedfatemi; Marjan Mardani-Hamooleh; Mansoureh Ashghali Farahani; AbouAli Vedadhir (BMC, 2023)
Abstract Background Characteristics of nursing care in the oncology ward depend on this ward's specific context. This study aimed to investigate the nursing care in the oncology ward regarding the culture of this ward. Methods This qualitative study was conducted in an oncology ward using a focused ethnographic approach. The whole nursing team of the selected ward (N = 16) participated in the study through purposeful sampling. Three methods of observation, interview, and field documents were used for data collection. Data were analyzed by Spradley's (1980) ethnographic method. Results 'Nursing in the oncology ward with intertwined roles' emerged as the main theme. This theme included the following subthemes: 'Robin Hood nurse,' 'a secretive nurse,' 'a negligent nurse,' 'a snitching nurse,' 'a complaining nurse,' 'an apathetic senior nurse,' 'a stigmatized training nurse,' 'a brazen-bodied nurse,' 'a compassionate nurse,' 'a moonlighting nurse,' and 'a drug bartender.' Conclusion This study provided a deep cultural insight into nursing care in the oncology ward, considering the particular culture of this ward and emphasizing the nurses' intertwined roles. These roles are on a spectrum, with positive roles, such as compassion, on one side and negative roles, such as negligence, on the other. The results of this study can be provided to nursing managers; therefore, by being aware of nurses' roles considering the specific subculture of the oncology ward, they can provide psychological interventions to improve the mental health of reluctant and complaining nurses and ethics-based training for secretive, negligent, and snitching nurses to provide quality care to the patient.